Developing an interactive e-module for digestive system materials to improve the analysis ability of high school students - Melati Astria Jayanti (Universitas Negeri Yogyakarta, 2023)
AbstractThis study aims to develop biology teaching materials for the digestive system in the form of interactive e-modules for high school students in class XI. The learning device development procedure in this study adapts the ADDIE procedure (Analysis, Design, Development, Implementation, and Evaluation). The development of learning tools begins with the stages of needs analysis, drafting, and validation. Validation is carried out through internal review steps, external reviews, and limited trials. The effectiveness of interactive e-modules on analytical skills was carried out through experimental research. This development research used an experimental one group pretest posttest design. The results of the study stated that the interactive e-module was in the good category. Then for the effectiveness of the interactive e-module on the material of the human digestive system, it effectively improves student’s analytical skills. The results of the N-Gain Score test showed that there was a difference between the scores before being treated using an interactive e-module and after being treated using an interactive e-module with an N-Gain Score of 0,48. According to the results of the N-Gain Score test, it can be concluded that the interactive e-module is effective in improving student’s analytical skills on the digestive system material in the medium cateory.Keywords: Interactive e-module, analytical skills, digestive system